Effects of VerifyNow P2Y12 test and CYP2C19*2 testing on clinical outcomes of patients with cardiovascular disease: A systematic review and meta-analysis. (August 2013) - Yamaguchi, Yusuke; Abe, Takayuki; Sato, Yuji; Matsubara, Yumiko; Moriki, Takanori; Murata, Mitsuru
<x xml:space="preserve">Abstract</x> The VerifyNow P2Y12 test is a whole-blood, light transmission-based optical detection assay that measures adenosine diphosphate-induced platelet aggregation in a cartridge containing fibrinogen-coated beads. The usefulness of this device to assess the effect of clopidogrel on platelet function was recently highlighted for predicting cardiovascular (CV) events. We therefore performed a meta-analysis to analyze whether adverse clinical outcomes of patients with CV disease increase in association with high on-treatment platelet reactivity (HPR) using the VerifyNow P2Y12 test. We also investigated the effect of the CYP2C19*2 polymorphism on the occurrence of CV events among clopidogrel-treated patients. Relevant studies were searched for in the PubMed database and Cochrane Central Register of Controlled Trials database, and selected if they included data about platelet function assessed using the VerifyNow P2Y12 test or CYP2C19*2 polymorphism in clopidogrel-treated patients with CV disease, and the occurrence of CV events within 6–12 months. In our meta-analysis, 4817 subjects from eight studies and 5307 subjects from seven studies were included for review of platelet function and CYP2C19*2 polymorphism, respectively. Overall, 2237 (46.4%) patients had HPR and these patients had significantly higher odds of CV events compared to patients without HPR (odds ratio(OR) = 3.05, 95% confidence interval: 2.33–3.98, p < 0.001). Heterogeneity among studies was not significant (Cochran's Q-test, p = 0.80 and I2 = 0%). In the secondary investigation, 1926 (36.3%) patients had at least one CYP2C19*2 allele. Heterogeneity in the OR of the CV events between the CYP2C19*2 allele carriers and non-carriers was observed among the seven studies (Cochran's Q-test, p = 0.01 and I2 = 56.5%), and the range of the ORs among the seven studies was 0.58–16.6. In conclusion, HPR assessed by VerifyNow P2Y12 test was associated with increased adverse clinical outcomes of clopidogrel-treated patients with CV disease.